2009
DOI: 10.1007/s11232-009-0113-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the QCD ground state in the Hartree-Fock-Bogoliubov approximation

Abstract: We study quark behavior in a strong stochastic gluon field. Based on the procedure of the averaged description, we derive the effective Hamiltonian and find its ground state in the Hartree-Fock-Bogoliubov approximation. We compare different model Hamiltonians. We discuss the chiral limit transition in detail in the example of the Keldysh model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 28 publications
(35 reference statements)
3
22
0
Order By: Relevance
“…The next curves and the ones following upwards correspond to temperatures T = 10 MeV, T = 50 MeV (an upper curve) with a step T = 10 MeV. Let us also remember that the pressure of the vacuum for the NJL model was estimated in [9][10][11] to be 40-50 MeV/fm 3 , which is quite consistent with that obtained in the bag model. It was also demonstrated that there is a region of instability within a certain interval of the Fermi momenta generated by the anomalous behavior of pressure d P/dn < 0 (see also [33][34][35][36]).…”
Section: Mean Energy As a Functional Of Quantum Liquid Theorysupporting
confidence: 80%
See 4 more Smart Citations
“…The next curves and the ones following upwards correspond to temperatures T = 10 MeV, T = 50 MeV (an upper curve) with a step T = 10 MeV. Let us also remember that the pressure of the vacuum for the NJL model was estimated in [9][10][11] to be 40-50 MeV/fm 3 , which is quite consistent with that obtained in the bag model. It was also demonstrated that there is a region of instability within a certain interval of the Fermi momenta generated by the anomalous behavior of pressure d P/dn < 0 (see also [33][34][35][36]).…”
Section: Mean Energy As a Functional Of Quantum Liquid Theorysupporting
confidence: 80%
“…It is the latter that is implied in a scenario of chiral invariance restoration under extreme temperatures higher than 100 MeV and with a highly diluted quark ensemble. We have already noted (see also [9][10][11]) that the momentum p θ , which corresponds to the strongest quark-antiquark attraction d sin θ/d p = 0, …”
Section: Mean Energy As a Functional Of Quantum Liquid Theorymentioning
confidence: 89%
See 3 more Smart Citations